2011
DOI: 10.1111/j.1532-950x.2011.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Performance Testing of Two Arcuate Oscillating Saw Blades Designed for Use During Tibial Plateau Leveling Osteotomy

Abstract: Our results favor the Synthes blade in terms of cutting performance and the Slocum blade in terms of wear resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The curvilinear saw produced by Synthes is thinner and has a uniform thickness across its width. The cutting performance of these 2 designs have been shown to vary in efficiency and durability, with the Synthes saw shown to be more efficient in cutting and the Slocum saw more durable. A saw of uniform width was also shown to generate less heat than a Slocum biradial saw .…”
Section: Discussionmentioning
confidence: 99%
“…The curvilinear saw produced by Synthes is thinner and has a uniform thickness across its width. The cutting performance of these 2 designs have been shown to vary in efficiency and durability, with the Synthes saw shown to be more efficient in cutting and the Slocum saw more durable. A saw of uniform width was also shown to generate less heat than a Slocum biradial saw .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the absence of macrovibrations, typical of rotary or oscillating instruments, make piezosurgery an advanced osteotomy technique especially suited for oral and maxillofacial applications. However, as piezo-surgical osteotomies take longer compared to conventional techniques [9], improvements have been introduced for bone cutting saw blades to provide faster, yet safe, and accurate osteotomy gaps [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thorough lavage was carried out while performing the osteotomy to try to limit this potential effect. Two relatively recent veterinary studies showed that the potential for bone thermal damage in tibial osteotomies never reached critical duration of damaging temperatures and that use of saline irrigation produced no significant effect on peak cutting temperatures 17,18 . Whether lavage is indicated during creation of the osteotomy during PAUL to limit thermal damage to the bone is a potential area for further study.…”
Section: Discussionmentioning
confidence: 99%
“…Whether lavage is indicated during creation of the osteotomy during PAUL to limit thermal damage to the bone is a potential area for further study. Similarly, use of a sharp saw blade is widely advocated during performance of osteotomy procedures, with excessive blade wear from re‐use in multiple procedures having the potential to increase temperature at the cutting interface 18 . Within our case series we did not record data regarding whether a new oscillating saw blade was used for each procedure, or whether saw blades were re‐used in some individuals, and given the clinical nature of the study, we did not make any attempt to measure temperature at the saw‐to‐bone interface intraoperatively.…”
Section: Discussionmentioning
confidence: 99%